1998
DOI: 10.1080/01621459.1998.10474103
|View full text |Cite
|
Sign up to set email alerts
|

Local Estimating Equations

Abstract: Estimating equations have found wide popularity recently in parametric problems, yielding consistent estimators with asymptotically valid inferences obtained via the sandwich formula. Motivated by a problem in nutritional epidemiology, we use estimating equations to derive nonparametric estimators of a "parameter" depending on a predictor. The nonparametric component is estimated via local polynomials with loess or kernel weighting; asymptotic theory is derived for the latter. In keeping with the estimating eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Ruppert and Wand (1994) examined local least squares estimators for nonparametric models and these estimators are the basis of our approach, although our setting is different. Carroll, Ruppert, and Welsh (1998) developed weighted estimating methods for nonparametric estimation in a general setting, and Severini and Wong (1992) and Severini and Staniswallis (1994) have developed a generalized profile estimating equation approach to semiparametric estimation. Huggins and Yip (1999) developed nonparametric estimators for capture-recapture experiments based on martingale estimating equations by regarding the population size at capture occasions near a time t as being locally closed.…”
Section: Introductionmentioning
confidence: 99%
“…Ruppert and Wand (1994) examined local least squares estimators for nonparametric models and these estimators are the basis of our approach, although our setting is different. Carroll, Ruppert, and Welsh (1998) developed weighted estimating methods for nonparametric estimation in a general setting, and Severini and Wong (1992) and Severini and Staniswallis (1994) have developed a generalized profile estimating equation approach to semiparametric estimation. Huggins and Yip (1999) developed nonparametric estimators for capture-recapture experiments based on martingale estimating equations by regarding the population size at capture occasions near a time t as being locally closed.…”
Section: Introductionmentioning
confidence: 99%
“…where d t is the number of distinct individuals captured in t . The approach of Carroll et al (1998) then suggests the following estimating equations…”
Section: Estimationmentioning
confidence: 99%
“…Lloyd and Yip (1991) found that f (k, t, K) follows a beta-binomial distribution conditional on the past capture history and constructed a martingale estimating equation to estimate the population size in closed populations. Following the approach of Carroll et al (1998), we modify equation (5.20) in Lloyd and Yip (1991) and apply their suggested weight function to obtain the estimating equations…”
Section: Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimation in model (2) can be done by local estimating equations (cf., Carroll, Ruppert, and Welsh, 1998). In the setting considered here, local estimation can be seen as a weighted generalized estimating equation (GEE) with working independence used in the fitting.…”
Section: Introductionmentioning
confidence: 99%